Microplastics and environmental effects: investigating the effects of microplastics on aquatic habitats and their impact on human health - Yarahmadi, Aref; Heidari, SeyedeMozhgan; Sepahvand, Parisa; Afkhami, Hamed; Kheradjoo, Hadis (Frontiers in Public Health, 2024)
Microplastics (MPs) are particles with a diameter of less than 5 mm. The disposal of plastic waste into the environment poses a significant and pressing issue concern globally. Growing worry has been expressed in recent years over the impact of MPs on both human health and the entire natural ecosystem. MPs impact the feeding and digestive capabilities of marine organisms, as well as hinder the development of plant roots and leaves. Numerous studies have shown that the majority of individuals consume substantial quantities of MPs either through their dietary intake or by inhaling them. MPs have been identified in various human biological samples, such as lungs, stool, placenta, sputum, breast milk, liver, and blood. MPs can cause various illnesses in humans, depending on how they enter the body. Healthy and sustainable ecosystems depend on the proper functioning of microbiota, however, MPs disrupt the balance of microbiota. Also, due to their high surface area compared to their volume and chemical characteristics, MPs act as pollutant absorbers in different environments. Multiple policies and initiatives exist at both the domestic and global levels to mitigate pollution caused by MPs.Various techniques are currently employed to remove MPs, such as biodegradation, filtration systems, incineration, landfill disposal, and recycling, among others. In this review, we will discuss the sources and types of MPs, the presence of MPs in different environments and food, the impact of MPs on human health and microbiota, mechanisms of pollutant adsorption on MPs, and the methods of removing MPs with algae and microbes.